ASPEK PASTORAL-KATEKETIS DALAM LITURGI PERKAWINAN - Rahawarin, Bernard A. (LOGOS: JURNAL PENDIDIKAN KEAGAMAAN KATOLIK, 2013)
This article critically observes and responds to the questions of the faithful about effectiveness of the Sacrament of Marriage: “Why the liturgy is often regarded as if it is a foreign rite in everyday life?” The answer is that the liturgy simply emphasizes the catechetical-liturgical aspects and is less able to explain its relationship with our daily life. Therefore, the necessary pastoral behavior outside the ‘moment of celebration’ is needed to transform and to concretize the liturgical-catechetical aspects into the ecclesial practices